Mechanical properties of treadmill surfaces compared to other overground sport surfaces - Colino, E.; Felipe, J. L.; Van Hooren, B.; Gallardo, L.; Meijer, K.; Lucia, A.; Lopez-Fernandez, J.; Garcia-Unanue, J. (Sensors, 2020)
The mechanical properties of the surfaces used for exercising can affect sports performance and injury risk. However, the mechanical properties of treadmill surfaces remain largely unknown. The aim of this study was, therefore, to assess the shock absorption (SA), vertical deformation (VD) and energy restitution (ER) of different treadmill models and to compare them with those of other sport surfaces. A total of 77 treadmills, 30 artificial turf pitches and 30 athletics tracks were assessed using an advanced artificial athlete device. Differences in the mechanical properties between the surfaces and treadmill models were evaluated using a repeated-measures ANOVA. The treadmills were found to exhibit the highest SA of all the surfaces (64.2 ± 2; p < 0.01; effect size (ES) = 0.96), while their VD (7.6 ± 1.3; p < 0.01; ES = 0.87) and ER (45 ± 11; p < 0.01; ES = 0.51) were between the VDs of the artificial turf and track. The SA (p < 0.01; ES = 0.69), VD (p < 0.01; ES = 0.90) and ER (p < 0.01; ES = 0.89) were also shown to differ between treadmill models. The differences between the treadmills commonly used in fitness centers were much lower than differences between the treadmills and track surfaces, but they were sometimes larger than the differences with artificial turf. The treadmills used in clinical practice and research were shown to exhibit widely varying mechanical properties. The results of this study demonstrate that the mechanical properties (SA, VD and ER) of treadmill surfaces differ significantly from those of overground sport surfaces such as artificial turf and athletics track surfaces but also asphalt or concrete. These different mechanical properties of treadmills may affect treadmill running performance, injury risk and the generalizability of research performed on treadmills to overground locomotion.